2007
DOI: 10.3168/jds.2006-557
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Evaluation of Freeze-Dried Kefir Starter Culture Production Using Whey

Abstract: An economic study is presented in which industrial-scale production of freeze-dried kefir starter culture is discussed based on results on a laboratory scale. Industrial scale-up was based on a 3-step process using 3 bioreactors of 100, 3,000, and 30,000 L for 300 kg of freeze-dried culture/d of plant capacity. The major cost component of the total investment was the freeze-drying machinery, which consisted of 57% of the total investment. Production cost was reduced from 15.4 euros/kg ($18.5/kg) to 2.9 euros/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 20 publications
0
6
0
2
Order By: Relevance
“…Kourkoutas et al . () subsequently reported that freeze‐dried kefir starter culture production using whey was evaluated as economical. In the literature, most of the studies dealt with kefir culture, which did not contain authentic kefir grains.…”
Section: Introductionmentioning
confidence: 99%
“…Kourkoutas et al . () subsequently reported that freeze‐dried kefir starter culture production using whey was evaluated as economical. In the literature, most of the studies dealt with kefir culture, which did not contain authentic kefir grains.…”
Section: Introductionmentioning
confidence: 99%
“…Cost Comparison with Freeze-Dried and Wet Kefir Biomass The investment cost in a similar study focusing on the development of a plant for the production of freeze-dried kefir was found to be 4-fold higher than that of pressed wet kefir, mainly due to the cost of the freeze-drying machinery [14]. This investment cost could however be reduced to 46% for the production of thermally dried cells according to the plant proposed in this study, while the production cost was estimated at 4.9€/kg same as that of freeze-dried cells and 3.5-fold higher than that of wet biomass production ( Table 4).…”
Section: Production Costmentioning
confidence: 96%
“…In a recent study, the economic features of an industrial-scale production of freeze-dried kefir starter culture were presented, based on laboratory-scale results [14]. The conclusion was that the investment cost required for freeze-dried kefir was 4-fold higher than that of pressed wet kefir production, mainly due to the cost of the freeze-drying machinery.…”
Section: Introductionmentioning
confidence: 98%
“…Consequently, scale-up processes were developed for potable and fuel-grade alcohol production [28] as well as for SCP and baker's yeast production from whey [29]. Kourkoutas et al presented an economic evaluation of an industrial scale whey fermentation assays [30]. Another research regarded the expansion of ultrafiltration for milk pre-concentration, which results in important quantities of milk concentration permeate, a low-value byproduct of dairy industry.…”
Section: Desalination and Water Treatmentmentioning
confidence: 98%